Aspergillus fumigatus exposure through a qualitative microbial risk assessment in the poultry industry - Gomes, Bianca (2023)
Currently, the prevalent airborne microorganisms in animal production facilities are poorly described in terms of quantity, composition, and risk category. Few studies have already evidence of Aspergillus fumigatus, belonging to the WHO critical priority group list (2022) in the poultry environment. To mitigate and reduce contaminants, global guidelines for what constitutes good microbiological indicators from environmental samples must be established. Quantitative microbial risk assessment (QMRA) is a novel method for estimating the risk of exposure to pathogens. So far, no research has been conducted to design QMRA that takes into account the risks associated with fungal contamination in poultry environments. This study aims to characterize Aspergillus fumigatus exposure through a QMRA in the poultry industry.